STUDY OF TECHNICAL STATE IMPACT OF BRAKE RETARDERS AT THE PROCESSING ABILITY OF HUMPS - Kozachenko, D. M.; Grevtsov, S. V.; Bolvanovska, T. V. (Science and Transport Progress, 2016)
Purpose. The research aims development of methods for calculating the estimated capacity humps for the loss conditions of brake power retarders. Methodology. The operation of humps is connected with large number of random factors, such as the characteristics of cuts, environmental conditions, the value of braking power implemented by retardants and others. In this regard, to research the set tasks the methods of simulation modeling and mathematical statistics are used. Determination of speed and motion time of cuts on the routes is carried out on the basis of rolling down modeling of their rolling down from the humps. Findings. If the brake power of retarders of the rolling down part of humps is not enough to stop the cuts, it should be provided the intervals during break-up to release the rolling routes from the preliminary cuts. The dependencies allowing to set the duration of these intervals were determined using the methods of the probability theory If the brake power of retarders at the rolling down part of humps and at the classification tracks is not enough to meet the requirements of the aimed regulation of the cuts rolling speed, it is necessary the use the additional brake shoes. The work develops the methods that on the basis of simulation modeling of the humping process allow one to set the desired value of the break-up duration increase. They ensure the traffic safety at the given number of car motion speed regulators. Originality. Authors firstly proposed the improved methods for determining the estimated capacity of humps. Unlike the existing ones, allow taking into account the technological limitations caused by the requirements of the humping process safety and can be used to assess the performance of the humps in the conditions of parametric failures of the retarders. Practical value. The use of the proposed methods allows assessing the influence of the retarders’ disrepair on the performance degradation of humps for the existing volumes of work.